Association of Physical Activity (Sport) and Quality of Life: A Literature Review - Sella DEVITA; Anetta MÜLLER (Editura Universităţii din Oradea, 2020)
Physical activity, especially in a form of sport, is known to improve life quality. Somehow studies comparing the effect of physical activity on quality of life in patients with health problems and healthy people are limited. The aim of this study is to provide an insight and evidence of association between physical activity and life quality in a group of people with health problems and a group of healthy people.